2010
DOI: 10.1111/j.1600-0404.2009.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, neuroimaging and neurophysiological features in addicts with manganese-ephedrone exposure

Abstract: Presynaptic neurons in the nigrostriatal pathway are intact in Mn-induced parkinsonism after prolonged abstinence from ephedrone. The diagnosis is principally based on clinical signs and the history of drug abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 28 publications
(38 reference statements)
2
37
0
Order By: Relevance
“…Eye movements in EP have been reported to be slow and mildly restricted in the vertical and horizontal plane [1], [5], [9], [14], however they have never been objectively studied with videooculography. The role of the basal ganglia in the control of eye movements has been supported by extensive evidence [15][17].…”
Section: Introductionmentioning
confidence: 99%
“…Eye movements in EP have been reported to be slow and mildly restricted in the vertical and horizontal plane [1], [5], [9], [14], however they have never been objectively studied with videooculography. The role of the basal ganglia in the control of eye movements has been supported by extensive evidence [15][17].…”
Section: Introductionmentioning
confidence: 99%
“…In Sikk et al 122 performed FDG PET in four former ephedrone addicts with extrapyramidal symptoms after long-term intravenous use of ephedrone (methcathinone) contaminated with high concentrations of Mn. All patients demonstrated a widespread, but heterogeneous, pattern of reduced FDG uptake within the basal ganglia and the surrounding white matter.…”
Section: Pet Studies In Human Subjectsmentioning
confidence: 98%
“…46,49,122 While SPECT has shown a progressive loss of DAT density in PD patients, 109 DAT studies in Mn exposure have been mixed. An early SPECT study demonstrated significantly reduced DAT levels in the striatum of two Mn-exposed workers by [123I]-b-CIT.…”
Section: Spect Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Mn neurotoxicity in humans has been reported in young drug abusers who used potassium permanganate in the formulations of homemade ephedron (Methcathinone), leading to clinical features of parkinsonism. 26,27 Inhalation and gastrointestinal absorption represent the two major routes for Mn absorption into the human body. 28 The absorption of Mn is tightly regulated with approximately 1-5% of ingested Mn being absorbed by the gastrointestinal tract, and 30-40% of inhaled Mn absorbed by the lungs.…”
Section: Sources Of Human Exposure To Mn and Its Transport To The Cenmentioning
confidence: 99%